Propuesta de medio digital periodístico como respuesta ante la creciente desinformación y fake news en medio de una pandemia mundial y una incierta coyuntura política-social en el Perú. - López Segura, Miguel Alberto (2020)
Disinformation and fake news are threats that affect the modern world due to the instantaneous nature of information. The current pandemic has revealed a large number of fake news distributed in the country, so we see a journalistic need to cover. This represents an opportunity for new journalistic media, who must reinvent themselves, to find a way to insert into a hyperinformed audience. Mistaken content is shared without being properly verified, so it is necessary to have an agent who is in the responsibility of validate, verify and deny information. Also, to analyze affirmations and statements of politicians and personalities of all kinds, such as content shared by social media and other channels. The challenge of journalism is to converge on new technologies. Therefore, it is necessary to also think about platforms like YouTube due to the new ways in how the audience consumes information.